An annotated bibliography of celebral palsy resources, 2000-2009 - Dacillo, Jimzon E.; Rosal, Rosvida R. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2009)
The problem of the scarcity of information about Cerebral Palsy, especially to the families with disabled members, is lingering in the Philippines. Even the basic status or the number of Filipinos afflicted with this disability is not accurate. The government has no concrete program regarding this case.
This study focused on providing an annotated bibliography of Cerebral Palsy resources covering the publications from 2000 to 2009. This collection was done to show the available local and foreign resources regarding the disability. Moreover, it aimed to determine the advancement in the field and the recent technologies that were available to researchers, health care professionals, and families afflicted with this disability in a particular time and setting. The progression in the local literature was also studied.
Out of the 383 materials that were gathered from four Medical Libraries (College of Allied Medical Profession (CAMP) and Dr. Florentino B. Herrera, Jr. Medical Library (FBH), College of Medicine University of the Philippines Manila, University of the East Ramon Magsaysay Memorial Medical Center College of Medicine (UERM), University of Santo Tomas Faculty of Medicine and Surgery, and St. Luke's Medical Center College of Medicine, William H. Quasha Memorial Foundation), three non-government organizations (The National Council on Disability Affairs (NCDA), Philippine Academy of Rehabilitation Medicine (PARM) and the (PCPI) or the Philippine Cerebral Palsy, Inc., and the open-access journals through http://www.portal.elib.gov.ph, only 81 local articles were found.
An analysis of the number of local and foreign publications revealed that there was an acute insufficiency of materials available in the Philippines. However, the continuous rise in the studies done about the disability in the international community further proved that there was a growing awareness about it and the need for more effective treatment practices were increasingly recognized.
Researchers, health care professionals and everyone concerned are encouraged to step up on the effort to do more studies that can provide new advancement in the field, particularly in the Philippines.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Celebral palsy -- Bibliography; Medical libraries -- Philippines -- Manila; Medical libraries -- Philippines -- Quezon City